THE ORIGIN OF JIRGA IN BALOCHISTAN: THE ORIGIN OF JIRGA IN BALOCHISTAN - Baloch, Mumtaz Ali (Hanken, 2018)
Jirga system has been one of the most important elements of the Baloch society for sixteenth century. The social and political problems had been solved by the Jirga. This article reflects the socio-political norms, value and tradition of Baloch culture. In this article the different periods of Jirga and its changing norms has been comprehensively discussed.